COVID-19 pandemic increased ESKAPEEc bloodstream infections and amplified carbapenem resistance in Chinese children: a multicenter surveillance study (2016–2023) - Li, Xiaoqiang; Xu, Hongmei; Wang, Cai; Zhao, Ruiqiu; Wu, Jiaying; Yu, Hui; Wang, Chuanqing; Fu, Pan; Deng, Jikui; Hua, Chunzhen; Chen, Yinghu; Zhou, Mingming; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study investigated the long-term trends in the distribution and antibiograms of ESKAPEEc pathogens in neonatal and pediatric bloodstream infections (BSIs), shifts in minimum inhibitory concentration (MIC) of vancomycin and linezolid in Staphylococcus aureus, along with the changing patterns of antimicrobial resistance phenotypes over time in China. This work provides a reference for the prevention and treatment of pediatric BSIs.MethodsA multicenter retrospective surveillance study was carried out from 2016 to 2023 at 12 tertiary pediatric hospitals across nine provinces and autonomous regions in China. The collected data were analyzed using GraphPad Prism 8 and WHONET 5.6. Temporal variations and linear trends were evaluated using chi-square or Fisher’s exact tests.ResultsA total of 10,051 ESKAPEEc strains accounted for 22.5% (10,051/44,675) of all BSIs, with 32.3% from neonatal BSIs and 67.7% from pediatric BSIs. The detection rate of ESKAPEEc pathogens increased for post the coronavirus disease 2019 (COVID-19) compared to the pre-COVID-19. Carbapenem resistance levels were 5.5% in Escherichia coli, 28.0% in Klebsiella pneumoniae, 16.0% in Enterobacter cloacae, 12.5% in Pseudomonas aeruginosa and 38.5% in Acinetobacter baumannii. Both Staphylococcus aureus and Enterococcus faecium remained fully susceptible to vancomycin and linezolid. Between 2016–2019 and 2020–2023, resistance to ceftazidime and gentamicin decreased in Escherichia coli and Klebsiella pneumoniae while resistance to imipenem and meropenem increased. Acinetobacter baumannii exhibited reduced resistance to most antibiotics except cefotaxime, levofloxacin and amikacin. Staphylococcus aureus displayed a declining resistance to macrolides and aminoglycosides but increasing resistance to fluoroquinolones, whereas Enterococcus faecium exhibited reduced resistance to all tested antibiotics. Compared to neonatal BSIs, Klebsiella pneumoniae from pediatric BSIs exhibited lower resistance to all β-lactams especially carbapenems (32.3% vs. 15.0%) while Acinetobacter baumannii displayed higher resistance to all tested agents. Methicillin-susceptible Staphylococcus aureus (MSSA) strains had lower vancomycin MIC ≥2 μg/mL levels compared to methicillin-resistant Staphylococcus aureus (MRSA) strains. Significant temporal differences were observed in MRSA isolates with linezolid MIC ≥2 μg/mL but not in MSSA isolates. The MIC50 of vancomycin in MRSA strains was either equal to or higher than in MSSA strains from 2016 to 2022. The most frequently detected bacteria in carbapenem resistance, extended-spectrum cephalosporin resistance, fluoroquinolone resistance and aminoglycoside resistance were Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli and Acinetobacter baumannii respectively.ConclusionsThe incidence of ESKAPEEc in BSIs has increased, and the rising resistance to imipenem and meropenem in Escherichia coli and Klebsiella pneumoniae underscores the need for continued surveillance. Carbapenems remain effective against Gram-negative ESKAPEEc, while vancomycin and linezolid remain effective against Gram-positive ESKAPEEc. Age-stratified strategies are essential to manage carbapenem-resistant Klebsiella pneumoniae in neonatal BSIs and carbapenem-resistant Acinetobacter baumannii in pediatric BSIs. The MIC values for vancomycin in MRSA strains remained stable over time, whereas a decreasing susceptibility trend to vancomycin in MSSA strains and linezolid MIC shifts were not observed. Our findings are expected to provide to treatment of bloodstream infections in children and evidence on best practices and resource sharing for policy consideration to healthcare providers at the local and international levels.